PEMBERDAYAAN IBU-IBU, BIDAN DAN KADER POSYANDU MELALUI PENYULUHAN TENTANG PEMBERIAN MAKANAN SEHAT UNTUK MENINGKATKAN GIZI DAN DAYA TAHAN TUBUH BAYI DAN ANAK DI DESA PENGOTAN KABUPATEN BANGLI - Rini Noviyani; N. P. Ariantari; Rasmaya Niruri; K. Widyani Astuti; S. Chandra Yowani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
The Community Services was held in Bangli Utara Public Health Facility, Pengotan district, Bangli. The purpose of this activity is to give information about balanced nutition and massage for babies to participants which are housewives, midwifery and posyandu staff in Bangli Utara Public Health Facility, Pengotan. They were expected to have better understanding about balanced nutrition compared to imbalanced nutrition and how to massage their babies. The methods used in this activity were deliver information about balanced nutrition and invited discussion also the baby massage practice trained to them. The result showed that participants were very interested in our program. It could be proved by their activity in discussion.Keywords: information, balanced nutrition, baby massage practice